2017
DOI: 10.2217/nmt-2017-0026
|View full text |Cite
|
Sign up to set email alerts
|

Patient-centered Decision Making in Amyotrophic Lateral Sclerosis: Where are we?

Abstract: Practice pointsr Amyotrophic lateral sclerosis patients are supported by models of patient-centered decision making delivered through specialized multidisciplinary clinics. r Advances in research have led to changes in service delivery, with new members added to the multidisciplinary team. r Developments in genetics research have increased the complexity of patients' choices for genetic testing. r User-designed decision support tools could improve communication between patients' families and clinicians, to neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 73 publications
0
4
0
2
Order By: Relevance
“…Effective information provision and patient education are considered two of the pillars of patient-centred care, a model of care considered appropriate for individuals with chronic conditions and complex health care needs such as MND [75], MS [76] and PD [77]. However, patients in the studies included in this review often expressed their dissatisfaction with both the amount and nature of information they received (or did not receive) during the delivery of their diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective information provision and patient education are considered two of the pillars of patient-centred care, a model of care considered appropriate for individuals with chronic conditions and complex health care needs such as MND [75], MS [76] and PD [77]. However, patients in the studies included in this review often expressed their dissatisfaction with both the amount and nature of information they received (or did not receive) during the delivery of their diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative studies and qualitative comments in quantitative studies sometimes highlighted the need for doctors to show more empathy. Patients often felt that their doctors did not approach such a serious diagnosis in a caring and sensitive way and were described as 'detached', 'very clinical' and 'insensitive' [31,38]. Similarly, Pavey et al [34] described that patients considered that doctors were unwilling to be personally involved and offer emotional support; a participant in the Hughes et al [33] study also reported feeling 'dehumanised'.…”
Section: Doctors' Empathymentioning
confidence: 99%
“…Additionally, it seems important to explore motivations and emotions underpinning patient preferences, but also possible cognitive deficits (30) and low health literacy which can negatively influence patient decision-making. Decision aids have been proven effective in supporting decision-making ( 33) and can combine patient information with questions prompting patients to reflect on their preferences to better prepare them to discuss the decision with HCP's (34). Finally, all respondents in our survey included the family of the patient in the decisionmaking process and provided patients and their families with relevant information.…”
Section: Tailored Patient Informationmentioning
confidence: 99%
“…Third, ideally, decision aids and other information should be developed together with patients to provide patient information and support patients in exploring their preferences, which can help physicians to better explore patient readiness and tailor decision-making to individual patient needs. This is not an easy process, but the research group of Hogden and colleagues in Australia provide a useful development pathway that could provide guidance (18,26,34,36). Fourth, prospective studies on gastrostomy in ALS should be conducted aimed at providing conclusive evidence on efficacy on survival, weight, and quality of life, and on optimal timing.…”
Section: Clinical and Research Recommendationsmentioning
confidence: 99%
“…Disse må forholde seg til at deres risiko for å utvikle sykdommen kan vaere betydelig økt og må ta stilling til om de ønsker prediktiv testing, som etter norsk lov krever genetisk veiledning. Usikkerheten rundt betydningen av både positive og negative funn gjør at denne verken kan gi friske slektninger et tydelig beslutningsgrunnlag før testing eller sikker avklaring av egen risiko når testresultatet foreligger (18). Dette skiller seg fra Huntingtons sykdom, der en negativ gentest utelukker sykdommen og et positivt funn også gir viktig informasjon om forventet prognose (19).…”
Section: Diskusjonunclassified